Conformational and Chiral Properties of Cyclic‐tri(N‐methyl‐meta‐benzamide) Bearing Amidino Groups. Issue 8 (24th June 2015) - Nishiyama, Shizuka; Urushibara, Ko; Masu, Hyuma; Azumaya, Isao; Kagechika, Hiroyuki; Tanatani, Aya
Abstract Cyclic triamides 4 bearing amidino groups at the meta position of the phenyl rings were synthesized, and their conformational properties in the crystal and in solution were examined. Compound 4a exists as a capsule‐type dimer of the enantiomers with a bowl‐shaped syn conformation in the crystal state. Compound 4 exists mainly in the syn form in solution, and chiral induction was observed upon addition of a chiral acid to a solution of 4a. Chirality 27:487–491, 2015. © 2015 Wiley Periodicals, Inc.